2001
DOI: 10.1034/j.1399-302x.2001.016003129.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the recognition of Porphyromonas gingivalis antigens in mice

Abstract: T-cell cytokine profiles, anti-Porphyromonas gingivalis antibodies and Western blot analysis of antibody responses were examined in BALB/c, CBA/CaH, C57BL6 and DBA/2J mice immunized intraperitoneally with different doses of P. gingivalis outer membrane antigens. Splenic CD4 and CD8 cells were examined for intracytoplasmic interleukin (IL)-4, interferon (IFN)-gamma and IL-10 by FACS analysis and levels of anti-P. gingivalis antibodies in the serum samples determined by enzyme-linked immunosorbent assay. Western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…The results of the present study have demonstrated that in general the percentages of cytokine-positive CD8 cells in the spleens of immunized mice were significantly higher than those of the CD4 cells, as has been reported previously [27,28]. Also, while the percentages of cytokine positive CD8 cells were increased for the most part compared with the control group, only the percentage of IL-4 + CD4 cells was increased in the two groups immunized with both F. nucleatum and P. gingivalis.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The results of the present study have demonstrated that in general the percentages of cytokine-positive CD8 cells in the spleens of immunized mice were significantly higher than those of the CD4 cells, as has been reported previously [27,28]. Also, while the percentages of cytokine positive CD8 cells were increased for the most part compared with the control group, only the percentage of IL-4 + CD4 cells was increased in the two groups immunized with both F. nucleatum and P. gingivalis.…”
Section: Discussionsupporting
confidence: 89%
“…While the strains of bacteria were different from those used in the present study, this does not explain the diverging results. As well, five times the dose of organisms was used in the former protocol, although the immunizing dose of P. gingivalis has been shown to have no effect on the T cell cytokine profiles of immunized mice [28]. T cell clones were not established in the present study, which may be partly responsible for the differences found in the two studies, although based on the splenic T cell profiles of the present study, both CD4 and CD8 specific T cells with a Th1/Th2 profile would possibly be expected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A mouse model has been used to define the immune response to P. gingivalis (29, 30) and variations in the local T- and B-cell responses occurred with different mouse strains. Interestingly, a study examining coinfection with P. gingivalis and Fusobacterium nucleatum demonstrated inhibitory effects on antibody production by both bacteria (31).…”
Section: Host–bacterial Interactions In Periodontal Diseasementioning
confidence: 99%